Executive summary of the KDIGO 2021 Guideline for the Management of Glomerular Diseases - Rovin, Brad H; Adler, Sharon G; Barratt, Jonathan; Bridoux, Frank; Burdge, Kelly A; Chan, Tak Mao; Cook, H Terence; Fervenza, Fernando C; Gibson, Keisha L; Glassock, Richard J; Jayne, David R W; Jha, Vivekanand; et al. (Kidney international, 2021)
The Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guideline for the Management of Glomerular Diseases is an update to the KDIGO 2012 guideline. The aim is to assist clinicians caring for individuals with glomerulonephritis (GN), both adults and children. The scope includes various glomerular diseases, including IgA nephropathy and IgA vasculitis, membranous nephropathy, nephrotic syndrome, minimal change disease (MCD), focal segmental glomerulosclerosis (FSGS), infection-related GN, antineutrophil cytoplasmic antibody (ANCA) vasculitis, lupus nephritis, and anti-glomerular basement membrane antibody GN. In addition, this guideline will be the first to address the subtype of complement-mediated diseases. Each chapter follows the same format providing guidance related to diagnosis, prognosis, treatment, and special situations. The goal of the guideline is to generate a useful resource for clinicians and patients by providing actionable recommendations based on evidence syntheses, with useful infographics incorporating views from experts in the field. Another aim is to propose research recommendations for areas where there are gaps in knowledge. The guideline targets a broad global audience of clinicians treating GN while being mindful of implications for policy and cost. Development of this guideline update followed an explicit process whereby treatment approaches and guideline recommendations are based on systematic reviews of relevant studies, and appraisal of the quality of the evidence and the strength of recommendations followed the "Grading of Recommendations Assessment, Development and Evaluation" (GRADE) approach. Limitations of the evidence are discussed, with areas of future research also presented.
Keywords: evidence-based; infection-related glomerulonephritis; dospělí; ledviny; Glomerulonephritis; anti-GBM; guideline; Glomerulonephritis, Membranous; membranózní glomerulonefritida; KDIGO; glomerulonefritida; Humans; nephrotic syndrome; lupus nephritis; MPGN; lipoidní nefróza; IgA vasculitis; complement; FSGS; glomerular diseases; membranous nephropathy; ANCA; Adult; IgA nephropathy; Nephrosis, Lipoid; Glomerulonephritis, IGA; glomerulonephritis; AAV; systematic review; Kidney; IgA nefropatie; lidé; dítě; Child; C3; minimal change disease